Evidences of Hierarchy of Brahmi Numeral System - Acharya, Eka Ratna (Journal of the Institute of Engineering, 2018)
The numeral system developed in South Asian Subcontinent in third century B. C. E. as the ancestor of the Hindu Arabic, Lichhavi, Kharosthi and other different numeral systems is popular by Brahmi numeral system. Ashoka prepared the pillar to preserve the Brahmi inscription with consisting numerals. The Brahmi numerical symbols are found at Lumbini of Nepal, for example a symbol used there tells the division by eight (Athabhagiya) and conversely multiplication of eight. Ashoka pillar with different inscriptions were found at Bihar, Uttarpradesh, Delhi, Madhyapradesh of India and different parts of Nepal like Niglihawa and Lumbini. In this system numerals are written from left to right. This system was very popular in South Asian Subcontinent for a long time and it impacts to the development of other numeral systems. The aim of this paper is to explore the hierchy and the existence of symbols of Brahmi numeral on the basis of document analysis and symbols found at different manuscript and monuments. Journal of the Institute of Engineering, 2018, 14(1): 136-142